Analysis of Productive Teachers Competence Drawing With Software in Vocational School - Yocky Syaida Adha Putra; Jalius Jama; Azwar Inra (Postgraduate School, Universitas Negeri Padang, 2020)
The research objective is to determine the competencies needed by productive teachers to draw with software so that graduates have the competencies desired by the business world and the industrial world. Descriptive qualitative research methods. The data in this research are descriptive narrative. Data sources from interviews, observations and documentation. The resource persons consisted of planning and supervision consulting firms, lecturers majoring in building engineering education at Padang State University and teachers teaching drawing with software at SMK N1 Padang and at SMK N1 SUMBAR. Data collection techniques with interactive and non-interactive. Data analysis techniques using qualitative techniques. Data validity is done by Source Triangulation. The results of the analysis: The teacher must master the science of drawing, cost estimation, time, quality and K3. The teacher must motivate and explain to graduates drawing with software how the work environment work environment. The teacher must teach good communication ethics and soft skills. The teacher must follow the development of software and also master its use. Teachers must be able to use IT to add references and self-development.